VIDEO TUTORIAL UNIT KOMPETENSI FACE TO FACE PADA PELATIHAN ONLINE METODOLOGI LEVEL 3 INSTRUKTUR DI BBPVP SERANG - Tia Norma Wulan; Aan Hendrayan; Rudi Haryadi (STKIP Subang, 2024)
Training is a total of activities to provide, obtain, improve and develop work competence, productivity, discipline, attitude and work ethic at a certain level of skills and expertise in accordance with the level and qualifications of the position or job. Trainers are instructors or other equivalent terms, who have the technical and methodological competence to conduct training. There are 3 forms of methodological training, namely offline training, blended/hybrid training, and online training. Therefore, one of the learning media uses LMS (Learning Management System). This year is the second year where 80% of training is full online. There are many challenges faced in implementing online methodology training because instructors and trainees do not meet in the real world so this different form of communication reduces the level of understanding of trainees. Data obtained from private instructor level 3 online methodology training stages IX and X in 2023 at BBPVP Serang. From the results of the initial data, it was obtained that the training course called the competency unit was considered the most difficult by the training participants, namely